The Bank Lending Channel: Evidence from Australia - Xin Deng; Luke Liu (Australasian Accounting, Business and Finance Journal, 2014)
This study explores how monetary policy changes flow through the banking sector in Australia. Drawing on data between 2004 and 2010, we divide banks into three groups according to their size, and examine the impact of that cash rate change on lending of different types of loans. We find the response of bank lending after a monetary policy change varies with the size of the bank as well as the types of loan. Smaller banks are more sensitive to policy rate changes, and household loans, government loans and intra-group loans are less responsive to monetary policy compared with financial and non-financial loans.